Land Use Change in a Pericolonial Society: Intensification and Diversification in Ifugao, Philippines Between 1570 and 1800 CE - Findley, David Max; Bankoff, Greg; Barretto-Tesoro, Grace; Hamilton, Rebecca; Kay, Andrea U.; Acabado, Stephen; Amano, Noel; Kaplan, Jed O.; Roberts, Patrick (Frontiers in Earth Science, 2022)
Land use modelling is increasingly used by archaeologists and palaeoecologists seeking to quantify and compare the changing influence of humans on the environment. In Southeast Asia, the intensification of rice agriculture and the arrival of European colonizers have both been seen as major catalysts for deforestation, soil erosion, and biodiversity change. Here we consider the Tuwali-Ifugao people of the Cordillera Central (Luzon, Philippines), who resisted Spanish colonial subjugation from the sixteenth to the mid-nineteenth century, in part through the emergence of a world-renowned system of intensive wet-rice terrace agriculture. To quantify changes in how the Tuwali-Ifugao used their environment, we model land use in Old Kiyyangan Village, a long-inhabited settlement, at two timepoints: circa 1570 CE, prior to the Spanish arrival in Luzon, and circa 1800 CE, before the village was sacked by Spanish military expeditions. Our model demonstrates that between 1570 and 1800 the adoption of rice as a staple and the corresponding expansion in terrace agriculture, along with a general diversification of diet and land use, enabled the village’s population to double, without increasing total land use area. This major intensification further led to the solidification of social hierarchies, and occurred without a proportional increase in deforestation.